Spatial water interaction in radium/uranium mines - a Portuguese case study - Antunes, Isabel Margarida Horta Ribeiro (2019)
The extraction of radioactive ore produces tailings and large volumes of waste rocks accumulated in the dumps. The abandoned Picoto radium mine area is located close to Vilar Seco village (Portugal). The mineralization occurs in quartz veins, with torbernite, meta-torbernite and uranophane, and some U-bearing minerals. The mine is in a soft slope area, with altitudes ranging from 360-380 m, included in the Cagavaio river catchment. The mining works were developed in surface and underground. First radium exploitation was carried out between 1917-21, in two open pit mines. Later, from 1950-53, the exploitation was reactivated, in underground galleries, to produce uranium. This mine was closed in 1953 and never has been restored. A local growing area was developed, mainly for vineyards and agricultural products. Three dumps contain about 35000 tonnes of wastes and is slightly covered by vegetation. A total of ten surface water and groundwater samples were collected. Most waters have pH values from 4.7 to 6.3 and are poorly mineralized (EC=45-224 µS/cm; TDS=17-150 mg/L). However, some waters are contaminated with NO2-, Fe, Mn, As and U. The drainage waters must be controlled within a temporal and spatial monitoring.